Six Essays on the Young German Novel - Sammons, Jeffrey L. (UNC Studies in the Germanic Languages and Literatures, 1972)
In this study of the prose fiction of Das Junge Deutschland, the internal stresses and paradoxes of specific texts are examined and special attention is devoted to the unfulfilled strivings toward realism. Following an introduction to the young German problem, with special reference to Wienbarg, there are essays on Gutzkow, Mundt, Kühne, and, as a contrast, the major novels of Immermann. The essays attempt to enhance the understanding of the post-Romantic crisis in German literature.